Effect Of The Organic Loading Rate On The Performance Of Mesophilic And Thermophilic Anaerobic Digestion Of Palm Oil Mill Effluent - Chou, Kian Weng (2011)
This project investigates the performance of mesophilic and thermophilic anaerobic digestion of palm oil mill effluent (POME). First, the scum-sludge mixture was acclimatized at mesophilic and thermophilic temperature prior the start-up of anaerobic digestion. The rapid CH4 production under both temperatures implied the anaerobic bacteria well adapted to POME. Later, the effect of organic loading rate (OLR) on anaerobic digestion of POME was investigated. The performance of mesophilic and thermophilic digestions were similar when OLR was ≤ 4.0 g COD/L/day. The average biodegradability of POME in mesophilic and thermophilic reactors was 77.14 % and 80.35 % respectively. Thermophilic reactor is more efficient because its maximum CH4 production rate (1.940 L CH4/L/day) was 53 % higher than mesophilic reactor (1.267 L CH4/L/day).